Drakoncjusz w więzieniu: siła poezji przeciwko sile władzy - Cichoń, Natalia (Vox Patrum, 2018)
In this paper I examine presumed reasons for the imprisonment of the Carthaginian poet of the fifth century A.D., Blossius Aemilius Dracontius. He wrote a panegyric for a dominus ignotus making a political faux pas – in the result Guntamund, the vandal king, imprisoned him – analyzing Dracontius’s poetry and taking into consideration the political and the cultural background I aim to find out who was the most probable recipient of the poem. These reflections lead in the conclusion to the presentation of the peculiar character of the agreement between Romano-African people and barbarians, mostly on the cultural and literary level. In his poetry Dracontius gives us very important message about the relations between the educated classes of both nations on the Vandal royal court – we can assume that in the Vandal Kingdom still existed literary patronage on a very similar basis as it existed earlier in the Roman Empire.